PETA KONSEP PADA PEMBELAJARAN IPA UNTUK MENINGKATKAN KETERAMPILAN BERFIKIR RASIONAL SISWA SD/MI - Astuti, Rini Nafsiati (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2009)
One of the efforts to increase the instructional effectiveness natural science is by developing meaningful learning strategy through the using concept mapping. The objectives of instructional natural science at elementary school is not only learning concept natural science but also to increase thinking and creativity such as recalling, imagining, classifying, generalizing, comparing, evaluating, analyzing, synthesizing, deducing, inferring, skill processused by the experts in order to get and developing nature science. Concept mapping strategy is one of alternative strategy that can give the results to reach learning objectives. With concept mapping, students could interlocked the natural science before and the new natural science by included concepts to the cognition and defined the relationship on an exibhit then united to the wider structure. The good conceptual understanding will help the students in their learning, until the students will be easier to understand the material they learn. Strategy using concept mapping to increase effectiveness science instructional viewed from achievement and students learning retention, suggested to science’s teacher to use concept mapping as one of learning tools. Using concept mapping after instructional is more suggested, although the other strategy more suitable.Keywords: concept mapping, natural science, thinking and creativity